PENGARUH KONDISI SISTEM DRAINASE, PERSAMPAHAN DAN AIR LIMBAH TERHADAP KUALITAS LINGKUNGAN (Studi kasus Kelurahan Kuningan Kecamatan Semarang Utara) - Oktiawan, Wiharyanto; Amalia, Setia (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2012)
Kelurahan Kuningan in the district of north Semarang meet with enviromental quality and people’s healthy degree decrease cause by poor drainage system, solid waste and waste water management. This  case  had  been  caused  several  disease  that  disturb  people’s  healthy.  The  purposes  of  this research was  to  know  the  existing condition  of drainage  system, solid  waste and waste  water in KelurahanKuningan, to know the influence of existing condition into enviromental quality and people’s healthy, to give an overcoming solution connected with PenyehatanLingkunganPemukiman program that  points  on  people  in  this  development  area.  Method  used  in  this  research  is  observation, questionaire and  interview, BOD concentration measurement  in drainage line and secondary  data collection include institution aspect, operational, financial, law and also people’s role. Results of this research show that BOD concentration in tertiary, secondary and primary drainage line is over from PP No.82 tahun 2001. Calculation results show the available pump is not enough to take the water debit from domestic rain that accumulated with domestic waste water, plus when the flood tide and flood from the higher area. The condition is getting worse by stucking trash in line that causing disease and  become  sediment.  Waste  water  distribution  system  in  this  area  is  not  appropriate  with  high density population and also public MCK as sanitation place is careless. That case caused the unclean enviromental and people have to expend extra money to take the medicine and to buy clean water. The  recommended  overcoming  solutions  are  formating the  pumping  team  and  public  MCK  team management,  increasing  pumping  capasity,  maintenance  budget,  exploiting  the  sediment,  3R program, waste water distribution system with communal system and public MCK fixed up.